2021
DOI: 10.3390/w13213010
|View full text |Cite
|
Sign up to set email alerts
|

Persulfate Process Activated by Homogeneous and Heterogeneous Catalysts for Synthetic Olive Mill Wastewater Treatment

Abstract: Wastewaters from the olive oil industry are a regional environmental problem. Their phenolic content provides inherent toxicity, which reduces the treatment potential of conventional biological systems. In this study, Sulfate Radical based Advanced Oxidation Processes (SRbAOPs) are compared with advanced oxidation processes (namely Fenton’s peroxidation) as a depuration alternative. Synthetic olive mill wastewaters were submitted to homogeneous and heterogeneous SRbAOPs using iron sulfate and solid catalysts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
(64 reference statements)
1
14
2
Order By: Relevance
“…The application of SR-AOPs was shown to be very effective in the treatment of agroindustrial wastewaters. For example, in the work of Domingues et al [18], the application of PS/Fe 2+ in the treatment of OMW achieved a total polyphenols removal of 63%.…”
Section: Sr-aopsmentioning
confidence: 99%
“…The application of SR-AOPs was shown to be very effective in the treatment of agroindustrial wastewaters. For example, in the work of Domingues et al [18], the application of PS/Fe 2+ in the treatment of OMW achieved a total polyphenols removal of 63%.…”
Section: Sr-aopsmentioning
confidence: 99%
“…Studies have reported that the activation of oxidants such as PMS can be carried out by homogeneous and heterogeneous catalysts to produce SO 4 ⋅ − and ⋅OH [66] . To identify active species in the MMT−CuFe 2 O 4 /PMS system, the employment of ethanol (EtOH) and tert‐butanol (TBA), as probe reagents, was considered.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that the activation of oxidants such as PMS can be carried out by homogeneous and heterogeneous catalysts to produce SO 4 *À and * OH. [66] To identify active species in the MMTÀ CuFe 2 O 4 /PMS system, the employment of ethanol (EtOH) and tert-butanol (TBA), as probe reagents, was considered. Ethanol has the ability to scavenging both * OH (1.2 × 10 9 -2.8 × 10 9 M À 1 s À 1 ) and SO 4 *À (1.6 × 10 7 -7.7 × 10 7 M À 1 s À 1 ), while TBA is an operative scavenger for * OH (3.8 × 10 8 -7.6 × 10 8 M À 1 s À 1 ).…”
Section: Rb5 Degradation Mechanismmentioning
confidence: 99%
“…Persulfate is a strong oxidizing agent widely used in environmental fields like water purification and soil remediation [1]. In its pure form, persulfate has relatively low reactivity; however, it can be activated, producing sulfate radicals (SO 4…”
Section: Introductionmentioning
confidence: 99%